Farmers' Perceptions About Health and Welfare Issues in Turkey Production - van Staaveren, Nienke; Leishman, Emily M.; Wood, Benjamin J.; Harlander-Matauschek, Alexandra; Baes, Christine F. (Frontiers in Veterinary Science, 2020)
Farmers play an essential role in the management of animals and ensuring their health and welfare. However, relatively little is known about the health and welfare-related issues farmers themselves find important in the turkey sector. As part of a larger study, a cross-sectional survey of turkey farmers was conducted in Canada to identify the main perceived reasons for culling, mortality, and carcass condemnations in their flocks. Additionally, farmers were asked to rate the importance of different health and welfare-related issues (i.e., mortality, aggressive pecking, disease, leg injuries, leg deformities, breast injuries, and varying body size) during their summer and winter production, as well as for the sector as a whole. A total of 83 responses were analyzed (response rate 20%). The most frequently mentioned reasons for the culling of turkeys included leg-related issues (90.0%), sickness (60.5%), and small body size (58.0%). The perceived reasons for mortality were most often unknown (59.7%), or related to cannibalism (41.6%) or dehydration (42.9%). The main reasons for carcass condemnations at processing were related to skin (33.8%) or subcutaneous conditions (64.7%). Leg deformities and mortality were considered the biggest issues for the turkey production sector. In general, farmers rated items as more of an issue when the question pertained to the sector as a whole rather than to their farm. These results increase our understanding of the health and welfare-related problems in turkey production that farmers find important. This can ultimately help focus research efforts in addressing these issues through improved management adaptations or breeding approaches, thereby improving both the well-being of farmers and birds.